Information technology control and audit - Senft, Sandra (Boca Raton, FL : CRC Press, 2017)
"Updated to address cloud computing, web-based applications, and server virtualization, the fourth edition of this bestselling text provides a comprehensive overview of IT controls and audits. It facilitates a fundamental understanding of IT governance, controls, auditing applications, systems development, and operations. Supporting and analyzing the COBIT model, the book prepares IT professionals for the CISA and CGEIT exams. With summary sections, exercises, review questions, and references for further readings, it promotes the mastery of the concepts and practical implementation of controls needed to effectively manage IT resources"-- |c Provided by publisher.
"Preface This book is designed to meet the increasing need for information technology (IT) and audit professionals to understand IT governance and controls required to manage this key resource. This book can be used by IT and audit professionals to gain an understanding of IT governance, controls and audit practices. This book aligns to and supports the Control Objectives for Information and Related Technology (Cobi T) model and assists in preparation for the Certified Information Systems Auditor (CISA) exam. Exhibit 1 provides a map of this text to the CISA exam. Exam (%) CISA Examination Content Areas to Model Curriculum (Undergraduate) IT Audit and Control IT Planning and Organization IT Acquisition Implementation IT Delivery and Support Advanced Topics Title and Description 14 The IS audit process Provides IS audit services in accordance with IS audit standards, guidelines, and best practices to assist the organization in ensuring that its IT and business systems are protected and controlled"-- |c Provided by publisher.
Includes bibliographical references (p. 627-638) and index.
Keywords: Information technology -- Handbooks, manuals, etc. -- Auditing